Mind the gap: Assessing the size and determinants of the life insurance gap - Olli Ropponen; Tero Kuusi; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2022)
Preparing for the monetary loss associated with premature death of the breadwinner has become more relevant during the COVID-19 pandemic. However, very little is known about how much of the financial vulnerabilities are covered by the life insurance holdings in different population groups. We employ unique individual-level life insurance data of the Finnish population to study the voluntary life insurances, the components of financial loss following from a death of a breadwinner, and the gap in death cover (life insurance gap) calculated as the difference of the two. We find that only about 10% of Finns have a voluntary life insurance, and that they are concentrated on married people, people of working age and with higher income. The largest insurance gaps are among young individuals, men, high income and highly educated people. We also find that the insurance behavior is poorly explained by the net losses following from a death.
Keywords: G22; H31; H55; J17; 330; Life insurances; Life insurance gap; Households; Social security; Forgone income